Control methodology and modelling of active fixtures - Bakker, Otto Jan (2010)
Fixtures are used to fixate, position and support workpieces, and are critical elements in manufacturing processes. Machining is one of these manufacturing processes, and this is often done by computer numerical control (CNC) machines. A major trend observed in production industry is that manufacturing is increasingly done in small batches in combination with a quick changeover from one product to another, in combination with a surge in automation. Several novel fixture concepts have been developed that allow for a reconfiguration of the fixture layout, such that different types of workpieces can be fixtured using the same fixture components. However, the initial novel fixturing concepts lacked accuracy, and, in addition, required long set-up times. Recently, a new fixturing concept has been developed, the so-called intelligent fixturing system. Sensors and actuators are integrated in an intelligent fixturing system, which allows for an automatic and precise reconfiguration of the fixturing elements. Additionally, the actuated fixture elements can be used to exert optimal clamping forces to minimise the workpiece deflection during the machining process, this is called active fixturing.